2009
DOI: 10.1080/03630260902862020
|View full text |Cite
|
Sign up to set email alerts
|

β-Thalassemia Mutations in the Iranian Kurdish Population of Kurdistan and West Azerbaijan Provinces

Abstract: The aim of this study was to investigate the prevalence and spectrum of beta-thalassemia (beta-thal) mutations in the population of Sunni Muslim Kurds in western Iran and to set up a prenatal diagnostic laboratory. Sixty unrelated Kurdish beta-thal patients identified in hematology clinics from different cities were studied. The mutations in 120 chromosomes were studied by polymerase chain reaction-amplification refractory mutation system and direct sequencing methods. We found fifteen beta-thal mutations, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 15 publications
4
17
3
Order By: Relevance
“…The IVS-I-5 anomaly is another Asian Indian mutation, which is the most frequent mutation in Pakistan, southern and southwestern Iran, and is also common in many Arab countries (7,16,20,22). The frequency of 8.1% in this study is comparable to that reported from Dohuk, but is rather higher than that of Iranian Kurds or the East Anatolia region of Turkey (9,10,13). On the other hand, codon 5, which has been considered as a Kurdish/Iranian β 0 mutation, was also observed in a significant proportion of cases in an earlier (10), as well as Iranian Kurds (9), but not from the East Anatolia region of Turkey (13).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The IVS-I-5 anomaly is another Asian Indian mutation, which is the most frequent mutation in Pakistan, southern and southwestern Iran, and is also common in many Arab countries (7,16,20,22). The frequency of 8.1% in this study is comparable to that reported from Dohuk, but is rather higher than that of Iranian Kurds or the East Anatolia region of Turkey (9,10,13). On the other hand, codon 5, which has been considered as a Kurdish/Iranian β 0 mutation, was also observed in a significant proportion of cases in an earlier (10), as well as Iranian Kurds (9), but not from the East Anatolia region of Turkey (13).…”
Section: Discussionsupporting
confidence: 88%
“…This mutation is the most common β-thal mutation in many eastern Mediterranean populations, including Turkey, Lebanon, Jordan and Syria (12)(13)(14)(15)(16), and has its highest frequencies in Cyprus, but its frequency gradually decreases in countries further to the east, with a distribution pattern almost opposite to that of IVS-II-1 (15)(16)(17)(18)(19)(20). However, such a high frequency in Kurds of northeastern Iraq is not shared by those from Dohuk or Iran with frequencies of 1.9 and 6.0%, respectively, but is comparable with those reported from northwestern Iranian populations (18.0%) (8)(9)(10).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations